Limitations of External Audit in Detecting Fraud: eFishery Case - Pakpahan, Larta Rovenia (Master of Accounting Universitas Trunojoyo Madura, 2026)
This article analyzes auditors’ failure to identify financial statement manipulation by highlighting audit scope, professional skepticism, and the concepts of reasonable assurance and the expectation gap in the eFishery case. This qualitative research uses a case study, analyzing data sourced from investigative news, public reports, and academic literature. The findings indicate that auditors received only summary Excel files without access to the core accounting system or independent evidence, limiting procedures to aggregate figures and failing to uncover systematic earnings manipulation. This failure is understood as a structural consequence of the audit mandate, not professional negligence. This study closes the research gap on fraud by greedy CEOs and governance of Indonesian startups, and recommends strengthening access to audit evidence, data-driven audit technology, and governance oversight.